2011
DOI: 10.1002/hpm.1117
|View full text |Cite
|
Sign up to set email alerts
|

What should the government do regarding health policy-making to develop community health care in Shanghai?

Abstract: Although there have been other policies interacting with the impact of GCP, GCP reforms implemented in the pilot districts at different times (as well as the later, standardized GCP system) have been effective in enabling CHCs to focus on providing quality public health services and appropriate medical treatment, rather than concentrating upon profit and loss. The impact of the standardized GCP system was further confirmed by cross-sectional comparisons of some broad indicators, in terms of medical cost, quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…13,14 The poor medication adherence can be due to a number of factors, such as multiple dose regimens, poor eye sights or hands disabilities in the elderly, 13,14 or in some countries, financial constraints 7 . In the present study, 65% of the patients reported poor medication adherence in the 4-week period prior to the interviews at our clinics.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 The poor medication adherence can be due to a number of factors, such as multiple dose regimens, poor eye sights or hands disabilities in the elderly, 13,14 or in some countries, financial constraints 7 . In the present study, 65% of the patients reported poor medication adherence in the 4-week period prior to the interviews at our clinics.…”
Section: Discussionmentioning
confidence: 99%
“…7 There is poor referral between primary, secondary, and tertiary care, resulting in disordered medical consultations. The current challenges include how to provide high-quality primary care.…”
Section: China -Shanghaimentioning
confidence: 99%
“…From a similar perspective, Yu et al . () focused on cross‐sectional comparisons of certain broad indicators: medical cost, the quality of medical service, and coverage of healthcare services. According to the OECD, four policy touch points in health systems can influence policy performance: health system inputs, health system design, monitoring mechanisms, and improvement systems, which include the perspectives of policy process and outcomes (OECD, ).…”
Section: Evaluation Research On National Health Insurance Policymentioning
confidence: 99%